Germination and Storage Studies on Buchanania barberi Gamble-A Critically Endangered Tree of Southern Western Ghats - Sabu, T.; Louis Jesudass, L.; Louis Jesudass, L.; Mohanan, N.; Mohanan, N. (Indian Forester, 2020)
Seed studies of an endangered tree species, Buchanania barberi from southern Western Ghats, were conducted to develop suitable methods for germplasm conservation. Reduction of initial moisture content from 27% to 18% and subsequent storage in closed polycarbonate bottles at controlled conditions (2Â°C) could prolong the viability of the seeds up to 10 to 11 months compared to natural conditions, the seed seems to be of intermediate nature. Germination trails at nursery level indicated that maximum germination percentage and germination index of 70% and 1.7 respectively, were registered in mist chamber.